Computational Aspects of Multiscale Simulation with the Lumped Particle Framework (Communications in Computational Physics, 2012)
First introduced in [2], the lumped particle framework is a flexible and numerically efficient framework for the modelling of particle transport in fluid flow.In this paper, the framework is expanded to simulate multicomponent particle-ladenfluid flow. This is accomplished by introducing simulation protocols to model particlesover a wide range of length and time scales. Consequently, we present a time orderingscheme and an approximate approach for accelerating the computation of evolution ofdifferent particle constituents with large differences in physical scales. We apply theextended framework on the temporal evolution of three particle constituents in sand-laden flow, and horizontal release of spherical particles. Furthermore, we evaluate thenumerical error of the lumped particle model. In this context, we discuss the Velocity-Verlet numerical scheme, and show how to apply this to solving Newton's equationswithin the framework. We show that the increased accuracy of the Velocity-Verletscheme is not lost when applied to the lumped particle framework.